RETENSI FORTIFIKAN VITAMIN A DAN β-KAROTEN DALAM MINYAK GORENG SAWIT SELAMA PEMASAKAN - Drajat Martianto; Nuri Andarwulan; Yoga Putranda (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2018)
This study was carried out to obtain information on fortificants (vitamin A and β-carotene) stability in fortified palm oil. Four types of fortified palm oils were used in this research: palm oil fortified with red palm oil or RPO (containing β-carotene) 47.08 IU/g, vitamin A (Retinyl palmitate) 56.59 IU/g, combination A (targeted concentration of 30 IU β-carotene RPO and 15 IU vitamin A) 45.65 IU/g and combination B (targeted concentration of 15 IU β-carotene RPO and 30 IU vitamin A) 45.95 IU/g. These fortified oils were then used for shallow frying and sautéing (stir frying). Tofu was used in shallow frying and the oil was reused three times each day for several days. Meanwhile, bean sprout was used for sautéing. The used oils after shallow frying was then analyzed for vitamin A and β-carotene retention, as well as its other cha-racteristics such as peroxide value and free fatty acid (FFA) content. The sauted sprouts was also ana-lyzed for its fortificants retention. The capacity of oil to retain vitamin A and β-carotene decreased over the repeated use in frying. During the first frying, the retention of fortificants was not significanly differrent (P=0.05). In the second and third frying, β-carotene was less retained than the vitamin A. Fortificant combi-nation A and B had similar stability. The peroxide value of the oils increased until the second frying, then decreased. Starting the fourth use, the FFA percentage has not increased much hardly increased. The highest yield of fortificant in sautéed sprouts was vitamin A (63.37%), followed by combination B (53.42%), combination A (50.60%), and RPO (34.86%). Sautéed sprout (150 g) contained fortificant contributing to the fulfillment of vitamin A adequacy of 32.71-92.93%.